Preliminary Phytochemical Analysis and Invitro Anti–viral Activity of Ethanolic extract of Whole plant of Tinospora cordifolia (Thunb.) Miers against Hepatitis-A Virus - Maddi, Ramaiah; Kandula, Venkata Lakshmi; Vallepu, Bhagyavathi; Navuluri, Hymavathi; Kolluri, Harshavardhan; Vunnam, Divya Teja (International Journal of Scientific Research in Biological Sciences, 2018)
Herbal product design refers to the process of developing, standardizing, processing, and validating an herbal product for the market. Hepatitis A is an infectious disease of the liver caused by the hepatitis A virus (HAV). There are no specific medicines to cure infection with hepatitis A. Hence, there is a need for the development of less toxic, more efficacious and cost-effective antiviral agents. The present work highlighted the invitro anti–viral activity of ethanolic extract of whole plant of Tinospora cordifolia (Thunb.) Miers against HAV. Ethanolic extract of the selected plant was prepared by soxhlet apparatus and rotavap. For the antiviral screening against HAV, toxicological effect of selected plant extract was determined through MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) cell proliferation assay using Huh-7 cell lines. The standard used is Camptothecin (CPT) at 25µG concentration. Plant extract was tested at 3.125 μg/mL, 6.25μg/mL,12.5μg/mL, 25 μg/mL and 50 μg/mL concentrations. The cell morphology was observed and recorded under microscope. The results clearly indicated the selected plant extract shows a dose dependent activity and it was maximum at 50 μg/mL concentration where it shows only 56.24% of virus viability and it was comparable to standard drug where it shows 43.01% of viability. Phytochemical screening of selected plant extract reveals the presence of different secondary metabolites like alkaloids, flavonoides, tannins, resins, steroids. Presence of these compounds in alone or combination might be responsible for the observed antiviral activity.